KEBERADAAN BAKTERI PELARUT FOSFAT DAN AKTIVITAS ENZIM FOSFATASE TANAH DAERAH PERAKARAN TANAMAN OBAT DARI KEBUN RAYA CIBODAS - Suliasih suliasih (BPPT)
A study was undertaken to investigate to occurance of phosphate solubilizing bacteria from rhizosphere soil samples of medicine plants in Cibodas Botanical Garden. 13 soil samples of medicine plants are collected randomly The result shows that 71 isolates of phosphate solubilizing bacteria were isolated, and 10 species of these organism was identified as Azotobacter sp, Bacillus sp, Chromobacterium sp, C.violaceum, Citrobacter sp. , Enterobacter sp., E. liquefaciens. Nitrosomonas sp., Serratia rubidaea, Sphaerotillus natans. Azotobacter sp. And Bacillus sp. Are found in all of soil tested. Conversely, Serratia rubidaea is only in the sample from rhizosphere of Plantago mayor The activity of acid alkaline phosphatase in soil tested ranged from 0.78 â€“ 60,18 ugp nitrophenole/g/h, with the higest values being recorded in soil sample from rhizosphere of â€œLavenderâ€.Keywords : phosphate solubilizing bacteria, soil enzyme phosphatase